Reappraisal of species attributed to Halicarcinus White, 1846 (Crustacea: Decapoda: Brachyura: Hymenosomatidae) with diagnosis of four new genera and one new species from New Ireland, Papua New Guinea - Poore, Gary C. B.; Guinot, Danièle; Komai, Tomoyuki; Naruse, Tohru (Zootaxa, 2016)
Species of Hymenosomatidae previously treated as species or junior synonyms of species of Halicarcinus White, 1846 are assigned to this and other genera. Halicarcinus is restricted to seven valid species; Rhynchoplax Stimpson, 1858, since 1980 synonymised with Halicarcinus, is now recognised with four species; four species are added to Micas Ng & Richer de Forges, 1996 (making five in total); and four new genera are erected: Culexisoma n. gen. (two species, one newly described), Lucascinus n. gen. (three species), Nasutoplax n. gen. (one species) and Stimpsoplax n. gen. (three species). The genera are distinguished primarily on features of the gonopod 1, interaction of the pleon with the thoracic sternal pleonal cavity, maxilliped 3, male cheliped, propodus-dactylus articulation of the ambulatory pereopods, and degree of fusion of the pleomeres. Species of Halicarcinus s.s. share a short trilobed rostrum, strongly curved gonopod 1 and free pleomeres. Some members of other genera may have a similar rostrum but typically have a long median projection with or without lateral angles or spines variously developed at the anterior margin of a supraocular eave. A lectotype of Hymenicus cookii Filhol, 1885 (now Halicarcinus cookii) is designated. A lectotype of Hymenosoma leachii Guérin, 1832, in Guérin-Méneville 1829–1837 (synonym of Halicarcinus planatus Fabricius, 1775) is selected in the interests of nomenclatural stability. Halicarcinus quoyi (H. Milne Edwards, 1853) is recognised as a senior synonym of the more widely used H. innominatus Richardson, 1949, which is itself a nomen nudum because it was erected without type designation. We also recognise Hymenicus marmoratus Chilton, 1882, as a junior synonym of Halicarcinus varius (Dana, 1851). Species of Rhynchoplax share a curved gonopod 1, falcate dactyli on pereopods 2–5 and fused pleomeres 3–4 in males and 3–5 in females. Species of Micas have a twisted gonopod 1 with the apex bent and only one or two subapical teeth on the dactylus of ambulatory legs. Culexisoma n. gen. is established for Halicarcinus ginowan Naruse & Komai, 2009, and a second species, Culexisoma niugini n. sp., from Papua New Guinea as type species. The genus is unique among these genera in having the male pleon not tightly engaging with the thoracic sternum, maxillipeds 3 not fully covering the buccal cavern and in having a strongly sexually dimorphic rostrum. Species of Lucascinus n. gen. share a male cheliped with ‘nut-cracker’-like fingers and free pleomeres in both male and female. Nasutoplax n. gen. differs from others in the erect lateral profile of the rostrum and in gonopod 1 with an unusual subterminal spinulose projection on its posterior face. Stimpsoplax n. gen. has a gonopod 1 with a swollen base and a narrow strongly twisted distal part, tapering distally to a curved apex. Each genus is diagnosed, all species are tabulated, some discussed in more detail, and generic diagnostic characters are illustrated.